Corruption, economic growth and globalization - Teixeira, Aurora Amélia Castro; Pimenta, Carlos; Maia, António; Moreira, José António (Routledge studies in the modern world economy, 2016)
Corruption, economic growth and globalization : an introduction / Aurora A.C. Teixeira -- Corruption, economic growth and globalization : the linkages -- Economic growth and the economics of corruption : a merge between tribes? / Aurora A.C. Teixeira and Sandra Silva -- Globalization and corruption : impacts and nonlinearities / Joseph Attila -- Corruption types and economic growth impacts : a globalized perspective -- Everyday opinions on grand and petty corruption : a Portuguese study / Gabrielle Poeschl and Raquel Ribeiro -- Corruption in China through the lens of Finnish firms / Päivi Karkuhnen and Riitta Kosonen -- Corruption and network relationships : theory and evidence from Thailand / Sirilaksana Khoman -- Quasi-corruption in public procurement : the case of Russian Federation / Andrey Ivanov -- Corruption and political party financing : the case of Serbia / Vanja Bajovic and Savo Manojlovic -- Corruption in public management in Brazil : a hidden, regional perspective / Rodrigo Miranda, César Silva and Fátima de Souza Freire -- Corruption prevention and control : towards a sustainable growth trajectory -- Opportunity as a factor in public sector fraud and corruption / António Maia -- Results-based management : an effort to prevent corruption in the Thai public sector / Orapin Sopchokchai -- Legal system related to corruption control and corruption causes in Thailand / Sirirat Vasuvat -- Fighting corruption with strategy / Pedro Nevado and Frederico Cavazzinni